Analysis of Islamic bank's performance and strategy after spin-off as Islamic full-fledged scheme in Indonesia - Siswantoro, Dodik (Elsevier Ltd., 2014)
This paper analyses the performance and strategy of Islamic banks after the spin-off and establishment of a full-fledged Islamic bank (separated from the parent bank).Siswantoro (2012) stated that one good strategy was to acquire a good conventional bank then convert it into a full-fledged Islamic bank. The research methodology used is descriptive with graph analysis (a) after spin- off and (b) after September 2010.The sample in this research is eight Islamic banks that were recently established as full-fledged Islamic banks. Most Islamic banks that have been converted in the full-fledged scheme could optimize some source of funding such as capital injection and increasing temporary investment deposit.Murabahah (selling activity) still dominated their loan due to low risk and fixed income.